Comparison of the Effects of Nintedanib and Pirfenidone on Pulmonary Function Test Parameters and Radiological Findings in Patients with Idiopathic Pulmonary Fibrosis: A Real-Life Study - Olcay Aycicek; Serra Keskin; Muhammed Haciosmanoglu; Funda Oztuna; Yilmaz Bulbul; Tevfik Ozlu (Medicina)
Background and Objectives: The aim of our study is to compare the effects of pirfenidone and nintedanib on lung function and radiologic findings in Idiopathic Pulmonary Fibrosis and to identify which drug is more appropriate for which patient group. Materials and Methods: The data of patients who were treated in our department for at least one year between 1 January 2010 and 31 December 2022 and who were started on pirfenidone or nintedanib treatment with the diagnosis of Idiopathic Pulmonary Fibrosis were retrospectively reviewed. The patients were divided into two groups—the nintedanib and pirfenidone groups—and both groups were compared in terms of progression in lung function tests (changes in FEV1, FVC, 6 MWT and DLCO values at the 3rd, 6th, 9th and 12th months compared to baseline values) and radiological findings (the presence of progression in findings such as ground-glass opacity, reticulation, honeycomb and traction bronchiectasis) within 1 year after diagnosis. Results: The study included 109 patients. The number of patients treated with pirfenidone (IPF patients) was 82 (75.2%) and the number of patients treated with nintedanib was 27 (24.8%). When the PFT values at 3, 6, 9 and 12 months were compared with the baseline values in both groups, there was no statistically significant difference in any parameter between the two groups. No significant difference was found in terms of radiological progression at the end of 1 year in both groups. Conclusions: The results of our study show that pirfenidone and nintedanib are equivalent in their effectiveness in preventing disease progression in patients with IPF.